2022
DOI: 10.3390/insects13030260
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Commercial Metarhizium- and Beauveria-Based Biopesticides for the Biological Control of Ticks in the USA

Abstract: There is a need for the development of sustainable, nonchemical tick management strategies. Mycoacaricide and mycoinsecticide product development worldwide has focused primarily on fungi in the genera Beauveria (Hypocreales: Cordycipitaceae) and Metarhizium (Hypocreales: Clavicipitaceae). Microbial biopesticides containing entomopathogenic fungi have potential in tick management. However, despite considerable progress in the development of fungal biopesticides over the past 20 years, the establishment of comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…This is consistent with the results of a previous study, in which entomopathogenic fungi were isolated from soil samples in Korea using the same selective medium as the experimental method of this study (Shin et al 2013). These two species are the most well-known entomopathogenic fungi, making them useful as biocontrol agents against a range of pests in numerous nations (Sullivan et al 2022). They are also the most often isolated species in many other nations (Sevim et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of a previous study, in which entomopathogenic fungi were isolated from soil samples in Korea using the same selective medium as the experimental method of this study (Shin et al 2013). These two species are the most well-known entomopathogenic fungi, making them useful as biocontrol agents against a range of pests in numerous nations (Sullivan et al 2022). They are also the most often isolated species in many other nations (Sevim et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The collection of Aspergillus, Fusarium, and Metarhizium from all environments confirms the wide distribution of these fungi in most regions of the world in different habitats, soil types, plants, and plant residues, in both air and water (Edel-Hermann et al, 2015;Heo et al, 2019;Glare et al, 2021). The presence of Metarhizium in all habitats, especially soybean, confirms reports of a strong association of species of this this fungus genus with soils in cultivated habitats, particularly field crops (Quesada-Moraga et al, 2007), and its relationship with different hosts, including forest and agricultural pests (Sullivan et al, 2022). The lower diversity of entomopathogenic fungi in soybean, with the presence only of this genus is, probably, due to fungicide use to manage diseases in this crop (Alves and Juliatti, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…However, an improved understanding of the pathogenicity of entomogenous fungi is a prerequisite for evaluating pest control efficiency. To date, some entomopathogenic fungi have been commercialized and widely used for pest management in greenhouses and fields, especially Beauveria bassiana [ 5 , 6 , 7 ]. Many studies have shown that B. bassiana has significant lethal effects on a variety of insect pests, such as Ostrinia furnacalis [ 8 ], Cylas formicarius [ 9 ], Bemisia tabaci [ 10 ], Lycorma delicatula [ 5 ], Frankliniella occidentalis [ 6 ], and Leptinotarsa decemlineata [ 4 ].…”
Section: Introductionmentioning
confidence: 99%